God and the world of signs Trinity, evolution, and the metaphysical semiotics of C.S. Peirce - Robinson, Andrew. (Philosophical Studies in Science and Religion, 2010)
Christianity has been described as "a religion seeking a metaphysic". Drawing on the philosophy of C. S. Peirce, Robinson develops a metaphysical framework centred around a 'semiotic model' of the Trinity. The model invites a fresh approach to the claim that Jesus was the incarnate Word of God and suggests a new way of understanding how nature may bear the imprint of the Triune Creator in the form of 'vestiges of the Trinity in creation'. Scientific spin-offs include a new perspective on the problem of the origin of life and a novel hypothesis about the evolution of human distinctiveness. The result is an original contribution to Trinitarian theology and a bold new way of integrating philosophy, science and religion.